KESELAMATAN KERJA DI PERSIMPANGAN: EVALUASI IMPLEMENTASI SISTEM K3 PADA BENGKEL BERSERTIFIKASI ISO 45001:2018 - Gustiawan, Willson; Yasmin, Fausiah; Primadona, Primadona (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
Health, Safety, and Environment (HSE) is a critical element in ensuring workplace security, especially in high-risk sectors such as automotive repair and maintenance services. This study aims to evaluate the implementation of HSE programs at the PT Pasoka Sumber Karya workshop in Padang, Indonesia. Using a descriptive qualitative approach, data were collected through field observation and semi-structured interviews with seven informants, including mechanics and certified HSE experts. The findings reveal that while the company has adopted an HSE management system based on ISO 45001:2018 and designated HSE personnel, implementation remains suboptimal. The primary issues include inconsistent use of personal protective equipment (PPE), limited employee training, lack of standardized documentation, and weak enforcement of safety procedures. Between 2020 and 2024, three work-related accidents were recorded—two minor and one moderate—indicating gaps in workplace safety practices. This study contributes to the HSE literature by highlighting the gap between formal HSE policies and actual field practices, even within certified organizations. The research recommends strengthening HSE culture through regular training, performance-based safety enforcement, and accessible emergency response facilities. The results provide practical insights for mid-scale automotive workshops and offer direction for future studies on the effectiveness of HSE systems in the professional service sector.